2008
DOI: 10.1161/atvbaha.107.157248
|View full text |Cite
|
Sign up to set email alerts
|

Four SNPs on Chromosome 9p21 in a South Korean Population Implicate a Genetic Locus That Confers High Cross-Race Risk for Development of Coronary Artery Disease

Abstract: Objective— Recent genome-wide association studies have identified 4 SNPs on chromosome 9p21 associated with CAD (rs10757274 and rs2383206) and myocardial infarction (MI: rs2383207 and rs10757278) in White populations in Northern Europe and North America. We aimed to determine whether this locus confers significant susceptibility to CAD in a South Korean population, and thus cross-race susceptibility to CAD. Methods and Results— … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
101
2
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(111 citation statements)
references
References 24 publications
4
101
2
4
Order By: Relevance
“…6,9 In addition, the present genome-wide exploration identified significant association near CDKN2A/B in East Asians, as previously reported in European-descent populations. 1,2,5,7,8 Of the three loci, which we claim to be associated with CAD in the Japanese GWA study (Table 2), the disease association at two loci -12q24 and 9p21 -have been reported in several Asian populations 10,11,26 and could be regarded confirmatory. Nevertheless, two novel findings are noted in our study: (1) the other locus within an HLA gene, HLA-DQB1, which is considered to explain the previous descriptions of CAD (in particular, MI) association signals on 6p21 in the Japanese 21 and (2) a pronounced association with MI, as compared with CAD, for the variants on 12q24.…”
Section: Discussionmentioning
confidence: 54%
“…6,9 In addition, the present genome-wide exploration identified significant association near CDKN2A/B in East Asians, as previously reported in European-descent populations. 1,2,5,7,8 Of the three loci, which we claim to be associated with CAD in the Japanese GWA study (Table 2), the disease association at two loci -12q24 and 9p21 -have been reported in several Asian populations 10,11,26 and could be regarded confirmatory. Nevertheless, two novel findings are noted in our study: (1) the other locus within an HLA gene, HLA-DQB1, which is considered to explain the previous descriptions of CAD (in particular, MI) association signals on 6p21 in the Japanese 21 and (2) a pronounced association with MI, as compared with CAD, for the variants on 12q24.…”
Section: Discussionmentioning
confidence: 54%
“…This analysis showed that these factors are highly relevant to CAD with an adjusted OR ranging from 3.00-6.06 (P < 0.05), indicating that they are risk factors for CAD in the Chinese Han population. Shen et al (2008a), studying populations from South Korea, observed that the rs10757274 and rs10757278 alleles were highly correlated with CAD with ORs of 1.29 (95%CI = 1.06-1.58) and 1.29 (95%CI =1.06-1.57), respectively. rs10757274 and rs10757278 are located near the CDKN2A and CDKN2B genes, which encode proteins with important roles in the regulation of many cellular processes, including cell proliferation, maturation, senescence, and programmed cell death.…”
Section: Discussionmentioning
confidence: 99%
“…This SNP was furthermore identified as a risk locus for ischaemic stroke (odds ratio = 1.59 (1.20-2.11), P = 0.004) 24,25 and sudden cardiac death (meta-analysis of six independent cohort studies: odds ratio = 1.21 (1.04-1.40), P = 0.01) 26 . We also identified a homozygous minor allele of rs2383206 (GG), which is another major CHD and ischaemic risk SNP with a hazard ratio of 1.26 (1.07-1.48) 23 and 1.30 (1.06-1.58) 27 , respectively. In combination with rs10757274 the risk for developing CHD almost doubles 28 .…”
Section: Snp Analysismentioning
confidence: 96%